Modelling Green Production Process in the Natural Dyes Batik Industry Using Cleaner Production Options - Siti Ajizah (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2021)
Sustainable production policy has encouraged batik industry to switch synthetic dyes to natural dyes. However, the production process still brings negative impacts on the environment as well as on humans. In order to solve this problem, the batik industry needs to develop green production model using cleaner production options. The purpose of this research is to design green production model for greening the natural dyes batik industry. The research was conducted in the natural dyes batik industry “Mbah Guru”. Mbah Guru batik industry is located in Lamongan, East Java. The research used a feasibility study by using Pay Back Period (PBP). The last decision making of cleaner production options was used Bayes Method to assess and determine cleaner production options based on technical, economical, and environmental aspects. The result showed that all of cleaner production options are feasible. "Fertilizer making from natural dyes" had the shortest payback period of 0,057 years and "two steps washing for all washing processes" had the longest payback period of 0,92 years. The highest criterion weight was the environmental aspect of 0.41 and followed by the economical aspect of 0.35. “Natural dyes wastewater reusing” became the most priority of the cleaner production options. The batik industry will be more profitable if it is able to properly implement the recommended process improvements so that the negative impacts, both the environment and on humans, can be minimized.